RADI-14. SPORADIC MENINGIOMAS OF THE PEDIATRIC POPULATION: A REVIEW OF NEURORADIOLOGICAL, NEUROPATHOLOGICAL, AND NEURO-ONCOLOGICAL ATTRIBUTES. Issue 2 (22nd June 2018) - Bhatt, Paraag; Dorris, Kathleen; Levy, Jean Mulcahy; Schneider, Kami Wolfe; Suttman, Alexandra; Donson, Andrew; Foreman, Nicholas; Kleinschmidt-DeMasters, Bette K; Spence, Nicholas; Neuberger, Ilana; Mirsky, David
Abstract: Sporadic meningiomas within the pediatric population manifest neuroimaging features that are poorly defined in the literature. We sought to establish a set of imaging features which may help lead to early diagnosis, as well as determine whether the imaging attributes, neuropathology, and clinical outcomes of sporadic meningiomas differ from those that occur in the context of neurofibromatosis type 2 (NF2). METHODS: A single center retrospective study was performed. Inclusion criteria consisted of diagnosis at ≤21 years of age, histological confirmation of meningioma (sporadic cases), and available pre-operative imaging. Patients were stratified by NF2 genetic status. Medical records served as the source for followup of clinic data and CT and MRI imaging features were re-reviewed. RESULTS: Twenty total meningiomas were reviewed for neuroimaging characteristics, representing multiple meningiomas in 5 patients (all NF2), and solitary meningiomas in 8 patients (all sporadic). The median age at presentation was 12 years (range, 10 months-19 years). Sporadic cases presented with more atypical imaging features including larger size, mixed cystic and solid appearance, presence of calcification, and more peri-lesional edema than did those with confirmed NF2. CONCLUSIONS: Sporadic pediatric meningioma imaging characteristics differ from those occurring in the context of NF2. Recognition of these features may help lead to early diagnosis and guide surgical planning and management.